Analysis of the Criminal Law Implications on the Sale of Marital Property Prior to the Agreement on Joint Property Division in Indonesia - Aswadi; Muhamad Adystia Sunggara (Journal of Law, Politic and Humanities, 2025)
The application of law regarding the embezzlement of marital property after divorce in Indonesia faces significant challenges. Marital property, regulated under the Civil Code and Law No. 1 of 1974 on Marriage, often becomes a subject of dispute when one party sells it without the consent of the other. This event is not always categorized as a criminal act of embezzlement, leading to legal uncertainty and harming the affected party, particularly women. This study adopts a juridical-normative approach with a descriptive method. Data were collected through literature review and documentation of legislation, legal doctrines, and court decisions. The findings reveal that the application of criminal law to embezzlement of marital property still has significant shortcomings. Although Articles 35 and 36 of Law No. 1 of 1974 regulate joint consent in the use of marital property, criminal sanctions are not consistently enforced. Regulations in the Compilation of Islamic Law (KHI) emphasize the importance of proving the status of the property and the obligations of spouses in division. Legal uncertainty in the application of criminal sanctions for cases of embezzlement of marital property indicates the need for reform. Strengthening the definition of criminal acts and applying a clearer principle of justice are necessary to ensure fair protection of all parties' rights.